Digital marketing strategies in graduate follow-up: analysis of the ESPOCH case - Poalacin Paucar , Jennifer; Naranjo Vaca , Myriam; Delgado Rodríguez , Carlos; Camacho Gaibor, Víctor (mktDESCUBRE; Vol 1 No 21 (2023): Twenty-first Edition (January - June), 2023)
This study focuses on analyzing the factors that impact the visibility and positioning of ESPOCH's graduate follow-up and job placement system in order to determine effective dissemination strategies in digital channels. The relevant variables that influence the effectiveness of digital marketing to position a product were examined, specifically in the case of a system aimed at polytechnic graduates. The methodology is mixed at a descriptive level, using an online survey applied to a sample of 316 graduates, it was possible to determine the level of positioning of the system. In addition, the results obtained allowed identifying the appropriate channels to implement digital marketing strategies, such as SEO, social networks and email marketing. The main findings reveal that the lack of digital dissemination has prevented the system from reaching its target audience, which highlights the importance of digital marketing to position the system by designing digital strategies adjusted to the preferences of polytechnic professionals. In this sense, it is concluded that the implementation of a digital marketing plan can significantly improve the system and ultimately contribute to the successful job placement of polytechnic graduates.